Review On Auto-Depth Control System For An Unmanned Underwater Remotely Operated Vehicle (ROV) Using Intelligent Controller - Mohd Aras, Mohd Shahrieel; Abdullah, Shahrum Shah; Abdul Azis, Fadilah (Penerbit Universiti, UTeM, 2015)
-